Kenduri, Selametan, Tahlilan, dan Maulid Nabi: Menakar Tradisi Lokal di Indonesia dalam Perspektif Islam: Kenduri, Selametan, Tahlilan, and Maulid Nabi: Assessing Local Traditions in Indonesia from an Islamic Perspective - Ilyas, Muhammad; Attamimi, Muhammad Iqbal; Muttaqin, Moch. Nurhidayatul; Soebahar, Halim; Amal, Khusna; Mursalim, Mursalim (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2025)
This article discusses the local traditions of Kenduri, Selametan, Tahlilan, and Maulid Nabi from the perspective of Islam Nusantara, focusing on their meanings, the Islamic values they embody, and the controversies surrounding these practices in Indonesia. This phenomenon illustrates the process of acculturation between Islamic teachings and established local cultural wisdom, but faces ideological polemics between traditionalist and reformist groups. The main issues addressed in this article are how these traditions are understood by the community, what Islamic values they contain, and how the controversies surrounding their legal status can be analysed in greater depth. The research method used is a literature study, reviewing various relevant literature to comprehensively analyse the four traditions. The results show that Kenduri, Selametan, Tahlilan, and Maulid Nabi contain Islamic values such as gratitude, togetherness, ukhuwah Islamiyah (Islamic brotherhood), and the strengthening of social morals. However, these traditions face controversy, particularly regarding whether they are sunnah or bid'ah, which creates tension between puritan and traditionalist groups. Further discussion reveals that Islam Nusantara offers a moderate model of religiosity, balancing text and cultural context, and supporting inclusiveness and social harmony.